2010
DOI: 10.1136/bcr.07.2010.3166
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade myofibroblastic sarcoma of the gingiva

Abstract: SummaryLow-grade myofibroblastic sarcoma is a malignant tumour from myofibroblasts, which has only recently become clearly defined. It represents a rare entity developing in the soft tissues of the head and neck. About 20 cases have been reported in the oral cavity, especially in the tongue and bone, while gingiva as the primary site has been described only once to date. Diagnostic methods include histology and immunohistochemistry.The present report concerns a case of a 37-year-old man who presented with a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Within the head and neck region, the oral cavity and tongue in particular has been suggested as a common site of occurrence . Treatment primarily involves surgical resection with clear margins . The role of radiotherapy with or without chemotherapy in the treatment paradigm of LGMS remains unclear .…”
Section: Introductionmentioning
confidence: 99%
“…Within the head and neck region, the oral cavity and tongue in particular has been suggested as a common site of occurrence . Treatment primarily involves surgical resection with clear margins . The role of radiotherapy with or without chemotherapy in the treatment paradigm of LGMS remains unclear .…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Table 2 , LGMS was located in the head and neck in 53 cases (51.5%); soft tissue 41 cases vs. bone 6 cases, trunk in 26 cases (25.2%); soft tissue 11 cases vs. bone 1 cases, and extremity in 24 cases (23.3%); soft tissue 12 cases vs. bone 7 cases. In the head and neck region, the most common site was the tongue [ 1 , 6 , 8 – 10 , 13 , 14 ], followed by the larynx [ 17 20 , 47 ], and gingiva [ 3 , 12 , 15 , 16 ]. LGMS was also observed in the mandible [ 10 , 23 ], face [ 23 ], skull [ 9 ], acoustic meatus [ 9 ], and deep tissue spaces, including the parapharyngeal space [ 28 ] as well as throughout the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to the LGMS in the upper aerodigestive tract, Meng et al [ 29 ] reported that owing to the diverse histologic appearance in the same tumor of myofibroblastic sarcoma; misdiagnosis may occur in small and superficial biopsy samples. Montebugnoli et al [ 12 ] also reported that an OIB must be performed, reaching an adequate submucosal depth because a misinterpretation can result from the specimen being sampled from the tumor surface, which contains mainly the granulation tissue-like and hypocellular areas but not the atypia hypercellular area. However, if the tumor location is trunk or extremity, CNB are sometimes preferable because of its convenience, which can be performed as day surgery under local anesthesia at the outpatient clinic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], the majority of LGMSs have occurred in adult patients, although there is a wide age distribution from infants to elderly. Similarly, there is controversy regarding the site predilection, as well as the fact that the majority of the reports show predilection to head and neck sites including the oral cavity [ 3 , 4 , 6 ], in contrast to a few reports that indicate extremities and trunk as the site of predilection [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%